The lost debate : German socialist intellectuals and totalitarianism - Jones, William D. 1906- (University of Illinois Press, 1999)
Strange defeat : leftist intellectuals and Weimar's collapse, 1928-33 -- Socialists in dark times : perspectives from exile, 1933-39 -- Varieties of antitotalitarianism : wartime theories and politics, 1939-45 -- Totalitarianism's temptations : into the cold war